PERANCANGAN DASHBOARDMONITORING PERFORMANSI OLT TELKOM REGIONAL 3 JAWA BARAT - Ghifarian, Risan Ahmad; Iqbal, Muhammad; Rokhayah, Rokhayah (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2023)
In observing the performance of the Telkom Regional III West Java OLT device, there were still several tools that were lacking and this was done manually. This research aims to create a monitoring dashboard website for the performance section of OLT devices. This design uses the bootstrap display in website development. By using microservices and Docker containers to make it easier to develop features and configurations, this dashboard was chosen because it uses a method with data collection that is faster, easier, more accurate and automatic. Based on the Tx power and Rx power level testing results obtained after analyzing and carrying out tests by taking the results from STO Cimahi, it got a green level value which indicates that the equipment in the area is in good condition, STO Rajawali got a yellow level value which indicates a warning. and must make updates or additions, STO Lembong gets a red level value which indicates that the device is damaged and must immediately replace the new device.